Advances and innovations in ultrasound-based tumor management: current applications and emerging directions - Rui, Li; Min, Qi; Xin, Meng; Yujun, Chen; Yihong, Gu; Ruilong, Yan; Bo, Wang; Tengfei, Yu (The Ultrasound Journal, 2025)
As a crucial medical imaging modality, ultrasonography has emerged as a pivotal tool for tumor diagnosis and treatment owing to its non-invasive nature, real-time imaging capability, and superior resolution. Recent technological advancements have demonstrated unique advantages in early tumor screening, staging, and localization. Contrast-enhanced ultrasound (CEUS), utilizing microbubbles (MBs) and nanobubbles (NBs) to target vascular biomarkers, significantly enhances tumor visualization and demonstrates high sensitivity in molecular imaging. Multimodal ultrasound (MU), incorporating techniques such as elastography and automated breast volume scanning (ABVS), achieves improved diagnostic accuracy when combined with MRI/CT. The applications of ultrasound in localized and systemic tumor therapy have expanded considerably. High-intensity focused ultrasound (HIFU) enables thermal ablation of solid tumors, while low-intensity focused ultrasound (LIFU) facilitates sonodynamic therapy (SDT) through reactive oxygen species (ROS) generation mediated by sonosensitizers. Ultrasound-assisted drug delivery systems (US-DDS) leverage MB/NB cavitation effects to enhance chemotherapeutic agent delivery efficiency, overcome biological barriers, including the blood-brain barrier, and modulate immune responses. These technological breakthroughs have provided novel therapeutic options for cancer patients, garnering significant clinical interest. This review systematically examines current applications of ultrasound imaging and therapy in oncology, evaluates its potential clinical value, analyzes existing technical limitations, and discusses future development prospects. The article aims to provide innovative perspectives for tumor diagnosis and treatment while offering references for clinical practice.